Living with permanent infertility: A German study on attitudes toward motherhood in individuals with Complete Androgen Insensitivity Syndrome (CAIS) and Mayer–Rokitansky–Küster–Hauser Syndrome (MRKHS). Issue 11 (2nd November 2018) - Fliegner, Maike; Richter-Appelt, Hertha; Krupp, Kerstin; Brucker, Sara Y; Rall, Katharina; Brunner, Franziska
Abstract: In this study the authors examined the issue of permanent infertility in two diagnoses of the diverse sex developments (DSD) spectrum: Complete Androgen Insensitivity Syndrome (CAIS) and Mayer-Rokitansky-KÏster-Hauser Syndrome (MRKHS). The participants with CAIS ( n = 12) was older, showed a lower wish for a child and was less distressed about their infertility compared to participants with MRKHS ( n = 49). Our data indicated an "indifferent" attitude toward motherhood in CAIS and an "ambivalent" attitude in MRKHS. Depression was frequent in both. Infertility is a source of distress. However, the two groups seem to cope in different ways. Comprehensive medical information and psychological support should be provided.